Employer brand image in an international context – a comparison between Germany and Portugal - Luchtenveld, Anne Charlotte (2015)
Research Problem – The internationalization and globalization led companies expend their business all over the world and within they have to deal with people from all nationalities. Companies have to be aware of the different cultures and implement them into their strategies. Moreover need companies in times of “war of talent” a strategy to attract the right applicants for their company. For that employer branding is one possible one. The implementation of such a strategy should not miss to include the cultural aspect to be more strong and successful. Purpose of the Study – Even there are recently studies about employer branding and its implementation the cultural aspect is missing in further researches. Therefore the following study was conducted to determine the relationship between this two factors - at the example of Portugal and Germany. Design/Methodology/Approach – A qualitative content analysis was based on six interviews and a quantitative study (n = 200) to analyze the research questions was conducted and hypotheses were derived from a literature review. The interpretation is based on statistical and qualitative analysis. Findings/Implications – In fact there is a relationship between employer branding and cultural aspects. Moreover it can be assumed, that Hofstede´s findings are still updated. While nationalty is playing a role for employer branding, has gender, if even, a minor influence to employer branding. Research Limitations – Due to the fact, that this is a master thesis with time restrictions, the studies have a limited amount of participants. Thus the studies are not representative; they are only giving a hint in a direction. Furthermore is the amount of analyzed country to small. To determine Hofstede´s dimension, it should be more an amount close to his 72 countries.